Aprepitant-loaded solid lipid nanoparticles: a novel approach to enhance oral bioavailability - Hussain, Mazhar; Farooq, Muhammad; Saeed, Muhammad Asad; Ijaz, Muhammad; Adnan, Sherjeel; Masood, Zeeshan; Waqas, Muhammad; Ishaq, Wafa; Ameer, Nabeela (Beilstein Journal of Nanotechnology, 2025)
Objectives of the present study are the development of aprepitant (APT)-loaded solid lipid nanoparticles (SLNs) using the polymers poloxamer 407 and β-cyclodextrin for enhanced solubility and their pharmacokinetic analysis. APT-loaded SLNs were prepared by the precipitation method and characterized by physicochemical studies including particle size and zeta potential measurements, drug content, encapsulation efficiency and solubility studies, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), in vitro drug release in 0.1 M HCl (pH 1.2) and phosphate-buffered saline (PBS, pH 7.4), and pharmacokinetic studies. The optimal formulation (APT-CD-NP4) containing the highest concentration of β-CD showed the highest drug solubility (93.50% ± 3.73%) in PBS (pH 7.4) and drug content (96.75% ± 0.24%); particle size, zeta potential, and polydispersity index of APT-CD-NP4 were 121.1 ± 0.72 nm, −18.8 ± 0.94 mV, and 0.15 ± 0.35, respectively. SEM analysis showed that APT was converted from the crystal state into an amorphous state after SLN preparation. FTIR results indicated compatibility between APT and the polymers. XRD, TGA, and DSC results indicated no physical interaction between drug and polymers. In vitro drug release studies showed that APT-CD-NP4 yielded the maximum drug release (98.89% ± 4.11%) in PBS (pH 7.4) and followed the Higuchi release model (with exponent n = 0.542), indicating non-Fickian diffusion (anomalous transport). The maximum concentration of drug in plasma and the bioavailability of optimal formulation APT-CD-NP4 were higher than those of pure APT. Therefore, the optimal SLN formulation APT-CD-NP4 is a promising tool for oral administration with sustained release to improve the bioavailability of the BCS class-IV drug APT.
Keywords: aprepitant; β-cyclodextrin; pharmacokinetic study; poloxamer; solid lipid nanoparticles